Mixed Adenoma Well-differentiated Neuroendocrine Tumor (MANET) of the Digestive System: An Indolent Subtype of Mixed Neuroendocrine-NonNeuroendocrine Neoplasm (MiNEN). (November 2018) - La Rosa, Stefano; Uccella, Silvia; Molinari, Francesca; Savio, Antonella; Mete, Ozgur; Vanoli, Alessandro; Maragliano, Roberta; Frattini, Milo; Mazzucchelli, Luca; Sessa, Fausto; Bongiovanni, Massimo
Abstract : Mixed neuroendocrine-nonneuroendocrine neoplasm (MiNEN) consisting of adenoma and well-differentiated neuroendocrine tumor (NET) has been recently defined as "MANET." However, the clinico-pathologic and pathogenetic features of this entity are not thoroughly studied. We examined the clinico-pathologic features of 12 MANETs by expanding their p53 and β-catenin expression profiles as well as the presence of microsatellite instability and KRAS, BRAF, and PIK3CA mutations in the 2 tumor components. In all cases, the adenomatous component represented the larger part of the lesions and the NET was localized in the deep central portion of polyps. In 9 cases the latter was represented by NET G1, in 2 by NET G2, and in 1 by NET G3. In all cases, the glandular and NET components were intimately admixed, with zone of transition between the tumor components. The NET component was p53 negative in all cases and 3 of 8 cases showed variable nuclear positivity for β-catenin. All patients with follow-up data were alive and free of disease after a mean follow-up time of 9 years. No mutations in KRAS, BRAF, and PIK3CA genes and no microsatellite instability were found in both tumor components. Review of the literature also identified 59 previously reported MANETs and no tumor-related death has been found. Like mixed adenoneuroendocrine carcinomas, a high-grade malignant form of MiNENs with a poorly differentiated neuroendocrine carcinoma component, a common origin for both tumor constituents may be hypothesized. Moreover, the current series provides evidence that MANET is an indolent disease that needs to be distinguished from aggressive high-grade MiNENs.